2002
DOI: 10.1046/j.1439-0434.2002.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Symptom Development, Phenolic Compounds and Morphological Defence Responses in Wheat Cultivars Differing in Resistance to Fusarium Head Blight

Abstract: Abstracts Development of Fusarium head blight, caused by Fusarium culmorum, was evaluated in seven winter wheat cultivars and one spring wheat cultivar in an outdoor pot experiment. Of the cultivars studied, only the spring wheat cultivar Frontana exhibited resistance against initial infection by the fungus. Significantly higher amounts of free phenolic compounds were found in the glumes, lemmas and paleas of Frontana prior to and at all sampling times after inoculation, in comparison to the winter wheat culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 27 publications
10
102
0
1
Order By: Relevance
“…Siranidou et al (2002) found that contents of ferulic acid in glumes of cv. 'Frontana' resistant to Fusarium was over 2-fold higher than in the sensitive cv.…”
Section: Discussionmentioning
confidence: 99%
“…Siranidou et al (2002) found that contents of ferulic acid in glumes of cv. 'Frontana' resistant to Fusarium was over 2-fold higher than in the sensitive cv.…”
Section: Discussionmentioning
confidence: 99%
“…Our present study, on grain from spring barley treated with a fungicidal preparation with tebuconazole as active ingredient, yielded similar results but the increase of DON levels was even more pronounced than in Magan's study. In other studies (HOPE et al 2000;SIRANIDOU & BUCHENAUER 2001), the levels of DON were also higher after treatment with a formulation containing azoxystrobin that was reported to be very effective in protecting Triticum durum against fusarioses (LANZELLOTTI 2002). In addition, azoxystrobin very effectively protected wheat (JENKYN & GUTTERIDGE 2002), spring barley (OVERTHROW 2002) and winter barley (COOKE et al 2002) against take-all disease.…”
Section: Resultsmentioning
confidence: 82%
“…HOPE et al (2000) had applied the fungicides azoxystrobin and propiconazol to wheat grain and found significantly increased production of DON in the presence of the fungicides. SIRANIDOU and BUCHENAUER (2001) stated that treatment of the plants with azoxystrobin reduced the disease index of spikes, but the DON content of the grain was higher than that of the untreated control. BAUER (2000) applied the fungicide Amistar (azoxystrobin) on wheat.…”
Section: Variation In the Production Of Trichothecene Mycotoxin Deoxymentioning
confidence: 99%
“…Siranidou et al (2002) reported a lower content of free phenols in spring wheat heads (below 700 µg·g −1 ), and demonstrated that the concentration of these compounds in spikes of cv. Frontana, resistant to FHB, was approximately threefold higher than in spikes of cv.…”
Section: Discussionmentioning
confidence: 95%
“…Phenols-saturated cell walls become more resistant to cytolytic enzymes produced by pathogens. Moreover, lignification slows down the diffusion of toxins contributing to pathogenesis, and restricts nutrient uptake by pathogens from the host cell (Siranidou et al 2002). The following enzymes take part in transformations of phenolic compounds in plants: phenylalanine ammonia-lyase, peroxidase and phenolic oxidases (Kunaeva 1986).…”
Section: Introductionmentioning
confidence: 99%